Zeitgenössische Kunst aus Afrika 14 Gegenwartskünstler aus Côte d´Ivoire und Bénin - Fillitz, Thomas (2002)
Contemporary art of Africa reached a wider audience in the aftermath of the Magiciens de la Terre exhibition (Paris 1989). This study of fourteen artists from Ivory Coast and Benin is based on ethnographic fieldwork in both countries (1997), during which I worked with several artists. In order to consider the reception of contemporary art of Africa in the European/North American art world, researches in London, Paris, and New York followed (1997, 1998). In Ivory Coast, I focused on a group of academically trained artists who belong to the Vohou Vohou movement which started in the early 1980s, and reached prominence in the 1990s. In Benin, I worked with artists who were not academically trained. One needs, however, to differentiate, as some had training as traditional artists, like the iron sculptures Calixte and Théodore Dakpogan, and adapted in the early 1990s their acquired skills to the creation of contemporary sculptures. Others, like Romuald Hazoumè and Georges Adéagbo, are self-trained. But they too interact with academically trained artists during residencies in various, West African or European countries. In the major part of the volume, I am presenting the artists: which materials they are working with, what are their stylistic characteristics, which ideas and reflections are informing their work. In a following chapter, I try to trace the artists' trajectories, the connections they are using in their work, be it to traditional stylistic canons, materials, techniques, and concepts, or to European modernism. In doing so, I adopt a situated perspective from these local art worlds (Abidjan and Cotonou/Porto Novo), in order to show the complexity of these creative artistic practices. Other chapters of the volume deal with the notions of the art world (Becker's sociological one and Danto's cognitive). From an anthropological viewpoint I argue for a combination of both notions. Becker's is important as to show the social, cultural, and economic aspects of the local art world. These aspects concern what is possible, or what is restricting the artistic endeavour. Danto's concept needs an adaptation, in as far as it is not an embedding of the works of these artists within the grand narrative of Occidental art history. Rather, the notion is used in the plural, as the focus is on local, regional, and transcultural connections of artistic practices. I thereafter argue against a universalising, hegemonic narrative of the European/North American art world. The other notion, which is discussed in the volume, is the one of 'contemporary African art.' Instead of analysing the notion from a theoretical perspective, I follow the artists, how they explain their art and its possible African character. This approach shows a wide continuum between a clear African dimension and one that considers contemporary art practices as encompassing without any regional specification. The final chapter deals with reflections about a modern, contemporary anthropology of art. Such an anthropology does not restrict itself to the study of ethnic arts but considers all art as its subject. In particular, it has to deal with contemporary art in its present, multiple expressions on the basis of ethnographic fieldwork. It may participate in wider discussions about global art (although the notion is not dealt with in the volume), from locally situated gazes. Context is a major topic in that respect. While former studies in the anthropology of art contextualised works of art by considering their functions and meanings, context is here as well considered as related to artistic practices, the connections to other skills, techniques, materials, styles, or ideas which are visualised in the work of art. I would like to express my gratitude to the 'Fonds zur Förderung der wissenschaftlichen Forschung' (FWF) which enabled the fieldworks, archival researches, and the publication of the present volume.